Inventory management of medicines used to treat non-communicable chronic diseases in public health clinics at Dikgale Community, Limpopo Province - Molope, Raesetja Engelina (My University, 2020)
Background: Non-communicable chronic disease contributes to premature mortality in SA, threatening the socio-economic development of the country. The efficient management of essential medicines supply at the clinic level is vital as stock-outs of the medicines increase morbidity and mortality. Objectives: The study aimed to identify and determine the challenges in the inventory management of medicine for the treatment of non-communicable chronic diseases at public health clinics in the Dikgale community of Limpopo province. Methods: The study used a cross-sectional quantitative research design; the purposive sampling technique was used, as it requires people with specific skills, knowledge, and expertise. A Pre-validated questionnaire was used to collect data from pharmacists, professional nurses, and transport personnel. Stock card utilization review and checklist were used to verify the answers obtained from the participants. Descriptive and inferential statistics were used to analyse the data collected. All these processes ensure that stock is always available and at optimal levels. The availability of stock at optimal levels is dependent on the personnel following SOPs. Results: In total, 40% of pharmacists indicated to have never trained nursing personnel on stock management, and 66.7% which, is the majority of nursing personnel, reported they have never been trained on stock management. Only 26.67% of medicines used for NCDs did not have stock cards. The study further found that the stock-card was not used every time a transaction was made. Thirty-nine (39%) percent of the respondents did not know how to quantify order quantities; this factor contributes to stock-outs experienced at clinics. All the clinics did not have a secure dedicated area. Deliveries are offloaded outside the medicine room. Conclusions: There is a training gap that needs to be closed to meet the minimum requirements as per GPP guidelines and also help to reduce medicine stock-outs as personnel will be well equipped to handle stock. In terms of inventory management and stock control systems, all primary healthcare sectors used a manual/paper-based inventory management system. Stock control systems are in place but were not always utilised and, processes are not consistent among staff members across clinics. With distribution, it would work better if nursing personnel dedicated a person to place and receive orders as discrepancies will be picked up sooner, and quantities will be sufficient to last until the next ordering date. None of the clinics complied with “Ideal Clinic” standards for infrastructure, storage, and inventory management.
Thesis (M.A. Pharm. (Pharmacy Practice) -- University of Limpopo, 2020
Keywords: Inventory management; Stock-outs; Non-communicable diseases; Medicine supply; Inventory control; Chronic diseases